PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS XII IPA SMAIT AL-ITTIHAD RUMBAI - Astika, Eliya; Roza, Yenita; Suhermi, Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to improve the learning process and the student’s mathematical problem solving skill by applying Problem Based Learning (PBL) model. The type of this research is Classroom Action Research with two cycles. The subjects of this research were students of class science XII. This study was conducted in the first semester of academic year 2017/2018. The research instruments used are mathematical learning instruments and instruments for collecting data. Mathematical learning instruments used in this study are Syllabus, Lesson Plans, and Activity Sheets. Data collection instrument used in this study is Observation Sheets and Mathematical Problem Solving Tests. Data analysis techniques in this study are descriptive narrative analysis of qualitative data and descriptive statistics analysis of quantitative data. The result of this study showed that the implementation of PBL improved the student’s mathematical problem solving skill. The mean of the student’s learning achievement in cycle I which is 66.18 had improved to 86.32 in cycle II. The improvement of student’s learning achievement founded for each indicator of mathematical problem solving skill: identifying the problem, formulating the problem, carrying out the plan to solve the problem, and interpreting the solution. This study concludes that the implementation of PBL improved the learning process and the student’s mathematical problem solving skill at class science XII SMAIT Al-Ittihad Rumbai. PBL model can be used as an alternative to learning, because through this learning can improve the learning process and mathematical problem solving skill of the students.Key Words: Problem Based Learning, Mathematical Problem Solving Skill, Learning Process